2016
DOI: 10.1007/s10840-016-0144-3
|View full text |Cite
|
Sign up to set email alerts
|

Time-limited cryomapping during tachycardia: improved long-term outcomes for cryoablation of AVNRT

Abstract: PurposeCryothermal ablation (CTA) for atrioventricular nodal reentrant tachycardia (AVNRT) is considered safer than radiofrequency ablation (RFA) since it eliminates the risk of inadvertent AV block. However, it has not been widely adopted due to high late recurrence rate (LRR). In an effort to improve LRR, we evaluated a new approach to cryothermal mapping (CTM): “time to tachycardia termination” (TTT).MethodsThis single-center study had 88 consecutive patients who underwent CTA using TTT for AVNRT. The CTA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…The techniques we employed have been described in detail previously . The technique can be briefly summarized as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques we employed have been described in detail previously . The technique can be briefly summarized as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The techniques we employed have been described in detail previously. [17][18][19] The technique can be briefly summarized as follows. If employed, an ICE catheter is advanced to image the heart and is positioned in the right atrium.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the efficacy may be explained by a strict cryomapping protocol of the disappearance of VAs within 20 seconds after starting cryomapping. 10 Another study also reported a successful cryoablation for VAs from para-Hisian region. However, cryotest (cryomapping) was attempted before the cryoablation only in 40% of the patients, and detailed approach and mapping protocol of the cryotest were not reported in their study.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, we reported that the VAs originating near the His bundle region were successfully eliminated by first‐line cryoablation in all 4 patients. Furthermore, the efficacy may be explained by a strict cryomapping protocol of the disappearance of VAs within 20 seconds after starting cryomapping 10 . Another study also reported a successful cryoablation for VAs from para‐Hisian region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation